Strategi Pengumpulan Zakat pada BAZNAS se-Sumatera Barat - Widi Nopiardo; Asrida Asrida (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study discusses the strategy of zakat collection at BAZNAS throughout West Sumatra. The collection of zakat at BAZNAS throughout West Sumatra is still not optimal, even though the potential for zakat is quite high. This type of research is field research with a qualitative approach. Data collection techniques through interviews and documentation. Data analysis techniques through data reduction, data presentation, and drawing conclusions. Data validity assurance techniques through triangulation. The results of the study revealed that the strategy for collecting zakat was carried out through cooperation, active socialization, and innovation.